Flood risk map analysis using geospatial AHP of flash flood in Muscat, sultanate of Oman / Salim Mohammed Humaid Rashid Alwaili - Rashid Alwaili, Salim Mohammed Humaid (2024)
The main objectives of this research is to assess the flood risk of Wadi Aday basin on coastal infrastructure and population, to develop a web - based GIS application and tools to view and analyze coastal flood risk and to propose DRR methods. The area that was selected is situated in Muscat, which is the capital of the Sultanate of Oman, and it contains the primary commercial sector of the city. The primary data that was used to conduct this study was aerial photography that was taken in 2012 and included outcomes such as DTM, DSM, contours, hydro network, and ground control points captured by field survey and photogrammetric software. On the other hand, the data that were used as the secondary data included the spatial maps, the population, and the runoff from the rainfall. It has been brought to the public's and decision makers' attention that the importance of remote sensing and GIS technique, along with other types of geospatial data, has been emphasised in order to present their significance in floods and to raise awareness among the general population.